2017
DOI: 10.1007/s00213-017-4729-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum lithium levels and suicide attempts: a case-controlled comparison in lithium therapy-naive individuals

Abstract: The present findings suggest that higher serum lithium levels may be protective against suicide attempts in lithium therapy-naive individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
9
1
Order By: Relevance
“…Additionally, this necessitates further clinical studies to confirm the aforementioned findings. For example, in the association between suicide rate and lithium in drinking water, we performed clinical studies [2,3] to directly confirm the indirect evidence from epidemiological studies [27][28][29][30] although we could not perform RCTs for that field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, this necessitates further clinical studies to confirm the aforementioned findings. For example, in the association between suicide rate and lithium in drinking water, we performed clinical studies [2,3] to directly confirm the indirect evidence from epidemiological studies [27][28][29][30] although we could not perform RCTs for that field.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the study by Kessing et al (2008), the researchers conducted a Poisson regression analysis, comprising dementia diagnosis as the outcome and the number of prescriptions for lithium, anticonvulsants, antidepressants, and antipsychotics as the variables of interest, with censoring during schizophrenia diagnosis, death, or at the end of the study period (31 December 2005). Continued prescriptions of lithium were associated with a decreased rate of dementia ([number of prescriptions]: [2][3][4], RR = 0.46, 95% CI 0.21-1.01; [5][6][7][8][9], RR = 0.38, 95% CI 0.16-0.86; [10][11][12][13][14][15][16][17][18][19], RR = 0.39 95% CI 0.19-0.81; [20~], and RR = 0.44 95% CI 0.23-0.85). Nonetheless, continued prescriptions of anticonvulsants, antidepressants, or antipsychotics were not significantly associated with a decreased rate of dementia.…”
Section: Standard Lithium Levels For Dementia Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from these epidemiological studies, Kanehisa et al 22 analyzed serum lithium levels of 199 patients including 31 patients with a history of suicide attempts, 21 patients engaging in self‐harm, and 147 control patients. There was a significant difference between the three groups, with patients with a history of suicide attempts having significantly lower lithium levels than control patients; this was however only found in males, not in females.…”
Section: Discussionmentioning
confidence: 99%
“…Case-control studies analyzing this have been reported. Kanehisa et al (2017[ 4 ]) reported that the adjusted OR (95 % CI) of subjects with a suicide attempt for a low serum lithium level was 0.228 (0.059–0.883). They considered that higher serum lithium levels might be protective against suicide attempts in lithium therapy-naïve individuals.…”
mentioning
confidence: 99%